PELATIHAN PENGELOLAAN MENAJEMEN KEUANGAN PADA UMKM PUSPA PINUNJUL - Elana Era Yusdita; Liana Vivin; Lina Anjaswari; Erinna Yulia Putri (SURAKARTA ABDIMAS JOURNAL, 2023)
Abstract There are still many MSME actors who face obstacles in managing administration and financial management which have an impact on difficulties in obtaining access to capital and also in managing financial management. Community service is carried out to 1) To raise awareness and put the responsibilities of MSME actors/entrepreneurs regarding the importance of managing finances properly so that it will be easier to evaluate the development of their business, (2) To equip the abilities and skills of UMKM Puspa Pinunjul actors, (3) so that they can use and implementing a simple financial management system that is easily implemented in groups so that it can improve the financial performance of business units, (4) To increase the Participant's ability to make budget plans so that they can maintain the business and can develop the business in accordance with the plan according to the purpose of establishing a business. Community service activities are carried out at the UMKM Puspa Pinunjul in Klumutan Village, Saradan District, Madiun Regency. The implementation method goes through 4 stages which include Coordination and division of team work, shared perceptions with partners, implementation of workshops and Evaluation. Participants consisted of 17 namely the chairman and members who were members of UMKM Puspa Pinunjul. The results obtained from community service are an increase in understanding related to financial management and a positive response to the usefulness of implementing activities. Keywords : Financial management, Training, SMEs, Business Units